The role of demand in the agroecological transition: an analysis of recent literature - Blare, T.; Roman, S.; Pozo Loayza, C. del; Borja, R.M.; Oyarzún, P.; Alem Zabalaga, M. (Elsevier, 2023)
Much of the attention of the agroecological (AE) movement has focused on the adoption of AE farming practices. While the utilization of these practices is essential to the AE transition, AE food systems will only arise when the demand for AE products emerges. This review synthesizes the research that has examined the role of demand in the AE transition. We explore what lessons have been learned in understanding consumer interest in products with AE attributes and how demand for AE products has helped spur or hinder the AE transition. We conclude with an analysis of the next steps in advancing our knowledge to better understand how to enhance the demand for AE products to build AE food systems.